Pengaruh Aplikasi Kompos Kulit Kopi Sanggabuana Terhadap Pertumbuhan dan Hasil Tanaman Kailan (Brassica Oleraceae L. Var, Nita) - Suryana Firdaus; Fawzy Muhammad Bayfurqon; Rika Yayu Agustini (Peneliti.net, 2023)
Coffee husk was one of the wastes generated from coffee bean processing, the used of coffee husk waste into compost was an alternative to reduce the amount of waste, besides the use of coffee skin compost can be a source of nutrition for kailan (Brassica oleraceae L. var.nita). The purposed of this study was to obtained the best dose of coffee husk compost so as to increased the growth and yield of kailan (Brassica oleraceae L. Var. Nita). The research was carried out in the new land of Singaperbangsa Karawang University, Pasir Jengkol Village, Majalaya District, Karawang Regency, from April 2022 to August 2022. The design used was a single factor randomized block design (RBD) with 6 treatments and 4 replications, namely K0 (Control), K1 (5 tons of coffee husk compost per hectare), K2 (10 tons of coffee husk compost per hectare), K3 (15 tons of coffee husk compost per hectare), K4 (20 tons of coffee husk compost per hectare), K5 (25 tons of compost coffee husks per hectare) so that there are 24 experimental units. The results showed that K5 treatment had a significant effect on kailan plants aged 28 DAP, with plant heights of 28.3 cm and leaf area of ​​350.2 cm. Meanwhile, the K1 treatment on the observation of the number of leaves had a significant effect on kailan plants aged 28 days after planting with 7 leaves. The K5 treatment had a significant effect on the wet weight of 592.8 g, the wet weight with roots 627 g and the plot weight of 140.5 g. The application of coffee husk compost did not have a significant effect on root length.